Current and Emerging Directions in the Treatment of Eating Disorders - Tiffany A. Brown; Pamela K. Keel (SAGE Publishing, 2012)
Eating disorders are a significant source of psychiatric morbidity in young women and demonstrate high comorbidity with mood, anxiety, and substance use disorders. Thus, clinicians may encounter eating disorders in the context of treating other conditions. This review summarizes the efficacy of current and emerging treatments for anorexia nervosa (AN), bulimia nervosa (BN), and binge eating disorder (BED). Treatment trials were identified using electronic and manual searches and by reviewing abstracts from conference proceedings. Family based therapy has demonstrated superiority for adolescents with AN but no treatment has established superiority for adults. For BN, both 60 mg fluoxetine and cognitive behavioral therapy (CBT) have well-established efficacy. For BED, selective serotonin reuptake inhibitors, CBT, and interpersonal psychotherapy have demonstrated efficacy. Emerging directions for AN include investigation of the antipsychotic olanzapine and several novel psychosocial treatments. Future directions for BN and BED include increasing CBT disseminability, targeting affect regulation, and individualized stepped-care approaches.